Analisa Kebisingan Pada Alat Berat Wheel Loader Wa-350 Berdasarkan Perbandingan Jarak 50, 100, 150 Cm Dan Kapasitas - Sihombing, Suriady; Nababan, Wilson Sabastian; Tampubolon, Miduk; Turnip, Cris Stevan (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2024)
Wheel loader is a tool that facilitates work by using hydraulic energy. Wheel loader testing is carried out by looking for noise data arising in the combustion chamber. There are several stages that must be done, namely the first step is to prepare a sound level meter as a noise detection device for heavy equipment, wheel loader, then take measurements with several variations in the distance between the combustion chamber and the sound level meter. In the next step we can find out the noise level read at the sound level meter with ideal, medium, and maximum rotation on the WA-350 wheel loader. So that the Noise Threshold Value according to Permenaker No. per-51 / MEN / 1999, ACGIH, 2008 and SNI 16-7063-2004 is 85 dB. So the noise produced by the Wheel Loader above the NAB Permenaker 104.7dB can cause tingling, unwell, hearing saturation, stomach pain, and circulatory problems. It is recommended that workers are required to use earmuffs or ear muffs.